A Rare Case of Macrophage Activation Syndrome in a Neonate - Rabindran Chandran; Hemant Parakh; Rajnesh Murkhy; Madan Mohan Rao (International Journal of Medical Research and Review, 2015)
Macrophage activation syndrome is excessive proliferation of macrophages associated with hemophagocytosis in bone marrow. It is characterized by fever >38.5oC for ≥7 days, splenomegaly, cytopenias (≥2 lineages), hypertriglyceridemia/ hypofibrinogenemia & hemophagocytosis. MAS occurying in neonatal period is very rare & only 2 sporadic case reports are available.We report a case of a neonate with MAS who presented with unremitting fever, hepatosplenomegaly, cytopenia, hyperferritinemia, with bone marrow suggestive of Hemophagocytosis.